Green and Health Constitution of Green Open Space and Its Implementation in Surakarta - Absori Absori (Journal of Global Pharma Technology, 2020)
Purpose: to find the essence from 1945 Constitution of the Republic of Indonesia Article 28H Paragraph (1) confirms that the right to obtain a good and healthy environment and good health services is part of human rights. Methods: this reaserch is a normative juridical methods and his research aimed at describing the Green Constitution in government policy regarding green open space and its implementation in Surakarta as an attempt to carry out the development and planning of the city that is environmentally friendly. This research was legal research conducted using a qualitative non-doctrinal approach. The results: showed that the Green Constitution that is friendly and perspective of the environment contained regulations and protections for environmental perspective. Based on data from the Regional Spatial Planning Coordinating Team (called TKPRD) Surakarta has 10% open space and the latest research conducted by the Geographic Information System (2015) of Surakarta has 9.17% green open space. Conclussion: The Municipal Government of Surakarta should provide green open space about what is mandated in Law by 30%.